Community participation for girls and women living with Rett syndrome. (June 2014) - Andrews, Jaimi; Leonard, Helen; Hammond, Geoffrey C.; Girdler, Sonya; Rajapaksa, Ruwani; Bathgate, Katherine; Downs, Jenny
Abstract Objective: To describe the relationships between impairment and contextual factors and community participation for girls and women with Rett syndrome. Methods: Data was collected from a questionnaire completed in 2009 by families participating in the Australian Rett Syndrome Database (n = 214). Univariate and multivariate logistic regression were used to analyse relationships between impairment, personal and environmental factors and community participation. Results: The mean age of the girls and women was 17.6 years (SD = 7.95, range 3 to 34 years) with 114 (53.3%) girls still at school and 100 (46.7%) women post school. Frequency of activities was influenced by level of walking, community support and maternal education. For girls living at home, participation in activities was associated with greater functional independence and higher levels of maternal education. Participation in recreational (90.1%), physical/skill-based (67.6%) and/or social (70.3%) activities was commonly reported by families, while self-improvement (17.6%) activities were less reported. Younger girls participated in activities mainly with family members and older girls more frequently participated with carers. Conclusion: Participation for girls and women with Rett syndrome could be enhanced by stronger local community supports. There are also needs for the implementation of policies that ensure resources are available and accessible by those communities most in need. Implications for Rehabilitation Service providers need to ensure that families with less social advantage are able to access activities in the community. Families may need additional supports to access opportunities for participation as their daughter grows older. Carers in day centre and group home settings need access to training and resources to confirm and support their role in providing opportunities for participation for women with Rett syndrome.